Centurial Changes in the Depth Conditions of a Regulated River: Case Study of the Lower Tisza River, Hungary - Amissah, Gabriel Jonathan; Kiss, Timea; Fiala, Károly (Journal of Environmental Geography, 2017)
The Tisza River is the largest tributary of the Danube in Central Europe, and has been subjected to various human interventions including cutoffs to increase the slope, construction of levees to restrict the floodplain, and construction of groynes and revetments to stabilize the channel. These interventions have altered the natural morphological evolution of the river. The aim of the study is to assess the impacts of these engineering works, employing hydrological surveys of 36 cross sections (VO) of the Lower Tisza River for the years of 1891, 1931, 1961, 1976 and 1999. The changes in mean depth and thalweg depth were studied in detail comparing three reaches of the studied section. In general, the thalweg incised during the studied period (1891-1931: 3 cm/y; 1931-1961: 1.3 cm/y and 1976-1999: 2.3 cm/y), except from 1961-1976 which was characterized by aggradation (2 cm/y). The mean depth increased, referring to an overall deepening of the river during the whole period (1891-1931: 1.4 cm/y; 1931-1961: 1.2 cm/y; 1961-1976: 0.6 cm/y and 1976-1999: 1.6 cm/y). The thalweg shifted more in the upper reach showing less stabile channel, while the middle and lower reaches had more stable thalweg. Although the cross-sections subjected to various human interventions experienced considerable incision in the short-term, the cross-sections free from direct human impact experienced the largest incision from 1891-1999, especially along the meandering sections.